Quantitative Bestimmung und dynamische Bewertung optimaler wirtschaftspolitischer Entscheidungen - Christophe Deissenberg; Siegmar Stöppler (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1976)
– This article offers an introduction to Quantitative Economic Policy, i.e. the use of econometric models together with mathematical optimization methods for the analysis and quantitative determination of optimal macroeconomic policy. The corresponding basic methodology, optimal feedback stochastic control of linear econometric modeis given a quadratic cost functional, is presented with particular regard to its practical application. The method is then applied for demonstration purposes to an econometric model of the Federal Republic of Germany.
Keywords: 330